PENGARUH ETIKA KERJA ISLAM TERHADAP PRESTASI KERJA MELALUI KOMITMEN ORGANISASI PADA PONDOK PESANTREN HIDAYATULLAH PATI - Subiyanto, Subiyanto; Machbub, Achmad (EQUILIBRIUM, 2016)
This study aimed to analyze the influence of Islamic work ethics on the work performance which is mediated by the organization commitment on Pondok Pesantren Hidayatullah Pati. The samples were taken using purposive sampling, 167 respondents. The results showed that the Islamic work ethic has an important role for the creation of organizational commitment which is expected to improve the overall performances. Islamic work ethic variable is an important variable in creating organizations commitment and board and employees’ work performance. The improvement of Islamic work ethic from the board and employees influences the organizational commitment; the improvement of Islamic work ethic from the board and employees will affect their work performances; the improvement of better organization commitment will have positive influence to the board and employees’ work performances.